Minimally invasive esophagectomy for Barrett’s adenocarcinoma - Asti, Emanuele; Bernardi, Daniele; Sozzi, Marco; Bonavina, Luigi (Translational Gastroenterology and Hepatology, 2018)
Minimally invasive esophagectomy has become the preferred approach for invasive Barrett’s adenocarcinoma because it can speed recovery and enhance patient’s quality of life. Multiple minimally invasive surgical techniques have been described during the last two decades. Preoperative staging, anatomy and physiological patient’s status, comorbidity, and experience of the surgical team should drive the choice of the surgical approach. The trans-thoracic Ivor Lewis esophagectomy, either hybrid or totally minimal invasive, remains the preferred approach in these patients. Lymph node yield and short-term clinical outcomes have proven similar to open surgery, while quality of life appears improved. To establish a minimally invasive esophagectomy program, a steep learning curve and a multidisciplinary approach are required in order to provide optimal staging, personalized therapy, and adequate perioperative care. The role of minimally invasive surgery in the treatment of invasive Barrett’s adenocarcinoma will continue to expand in synergy with enhanced recovery after surgery pathways.